ANALISIS PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT FACILITATOR AND EXPLAINING DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK - Dewi, Eka Komala; Winata, Hendri (Universitas Pendidikan Indonesia, 2018)
Critical thinking skill of students is affected by many factors, including the learning model. There are many kinds of learning model; one of it is cooperative learning model with student facilitator and explaining type. This article discussed the results of research on the application of the student facilitator and explaining model in improving critical thinking skill of students in introduction of office administration subject. This study used a quasi-experimental method with Nonequivalent Control Group design. The results of conducted research showed a positive and significant difference in the application of the cooperative learning model with student facilitator and explaining type to improve critical thinking skill of learners.ABSTRAKKemampuan berpikir kritis peserta didik dipengaruhi oleh banyak faktor, diantaranya adalah model pembelajaran,dimana model pembelajaran ini banyak sekali macamnya salah satunya adalah model cooverarative learning tipe student facilitator and eksplaining. Artikel ini membahas hasil penelitian tentang penerapan model student facilitator and eksplaining dalam meningkatkan kemampuan berpikir kritis peserta didik pada mata pelajaran pengantar administrasi perkantoran. Dalam penelitian ini menggunakan metode eksperimen semu (quasi experiment) dengan desain Nonequivalent Control Group. Hasil penelitian yang dilakukan menunjukkan adanya perbedaan yang positif dan signifikan dalam penerapan model pembelejaran kooperatif tipe student facilitator and eksplaining untuk meningkatkan kemampuan berpikir kritis peserta didik.